Lead, cadmium and mercury levels in pregnancy: the need for international consensus on levels of concern. (28th November 2013) - Taylor, C. M.; Golding, J.; Emond, A. M.
Abstract : For heavy metals that have any degree of transfer though the placenta to the fetus, it is unlikely that there are safe limits for maternal blood levels. The only means of reducing fetal exposure is to minimise maternal exposure. There are few recommendations for levels of concern. With the exception of US recommendations for maternal Pb levels, but there are no international levels of concern or cut-off levels specifically for pregnancy for heavy metals, so that comparisons can generally only be made with national reference values relating to similar physiological statuses or age groups. These include recommendations for Cd levels by Germany (reference value for non-smoking adults aged 18–69 years, 1 µg/l) and for Hg by Germany (reference value for adults age 18–60 years with fish intake ⩽3 times per month, 2.0 µg/l) and the USA (cut-off level for women, 5.8 µg/dl). To illustrate the lack of cohesion, we present data on blood Pb, Cd and Hg levels from pregnant women enroled in the UK Avon Longitudinal Study of Parents and Children study and compare the values with present levels of concern and recommended cut-off values. We also compare the levels with those found in other groups of pregnant women worldwide to strengthen the database for the development of levels of concern in pregnancy. The need for clarity of terminology in describing levels of concern is discussed. There is a pressing need for international consensus on levels of concern for all age groups and physiological statuses, particularly for pregnancy.